2009
DOI: 10.1002/jnm.731
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Terahertz detection in self‐switching diodes

Abstract: SUMMARYIn this work, by means of Monte Carlo simulations, we analyze the presence of a resonance in the DC current response of an asymmetric nonlinear nanodiode (called self-switching diode) to AC voltage excitations in the Terahertz range. The phenomenon, which takes place at room temperature, can be enhanced and tuned by the geometry of the device, being potentially useful for selective Terahertz detection. The resonance is linked to a noise mechanism: collective charge fluctuations in the space-charge regio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Previous works of our team, performed by means of Monte Carlo (MC) simulations, have already explained the physics of the DC and AC operation of SSDs as well as their noise properties. 10,11 Regarding to their operation as Gunn diodes, it has also been shown that the nucleation and fast transit of high-field domains is promoted by the shape of the SSD. 9 Prior works of our group 12 have demonstrated the technological feasibility of GaN SSDs and foresee the possibility to generate power in the sub-THz frequency band.…”
mentioning
confidence: 99%
“…Previous works of our team, performed by means of Monte Carlo (MC) simulations, have already explained the physics of the DC and AC operation of SSDs as well as their noise properties. 10,11 Regarding to their operation as Gunn diodes, it has also been shown that the nucleation and fast transit of high-field domains is promoted by the shape of the SSD. 9 Prior works of our group 12 have demonstrated the technological feasibility of GaN SSDs and foresee the possibility to generate power in the sub-THz frequency band.…”
mentioning
confidence: 99%
“…Equations (2)-(7) are consistent with design dependencies that have been observed previously: Enhancing C h , for example, by reducing W h , can be expected to increase c i and thus b opt , which has been confirmed by MC simulations. 13 It has further been reported that b opt in SSDs is enhanced when W is decreased. 5,6 The model derived above quantifies this effect.…”
mentioning
confidence: 92%
“…They are listed as [2][3][4][5][6][7][8][9][10][11][12]. Particular attention was paid for showing the most representative contributions of each conference topic.…”
Section: Photovoltaic Optoelectronic Devices and Displays (21 Contrimentioning
confidence: 99%